2015
DOI: 10.1155/2015/471216
|View full text |Cite
|
Sign up to set email alerts
|

The Organotypic Longitudinal Spinal Cord Slice Culture for Stem Cell Study

Abstract: The objective of this paper is to describe in detail the method of organotypic longitudinal spinal cord slice culture and the scientific basis for its potential utility. The technique is based on the interface method, which was described previously and thereafter was modified in our laboratory. The most important advantage of the presented model is the preservation of the intrinsic spinal cord fiber tract and the ventrodorsal polarity of the spinal cord. All the processes occurring during axonal growth, regene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 32 publications
(33 reference statements)
1
12
0
Order By: Relevance
“…It is important to start the concrete experiments about 12-14 days after the beginning of OTS cultivation [24]. In some studies, the time of OTS culture before starting the actual experiment is shorter (1 week) [25,26]; so the mechanical damage caused by slicing disappears, and the cells can reach a more advanced developmental stage. In addition, this time period will allow the slices to acclimatize to the culturing conditions and mature.…”
Section: Organotypic Slicesmentioning
confidence: 99%
See 2 more Smart Citations
“…It is important to start the concrete experiments about 12-14 days after the beginning of OTS cultivation [24]. In some studies, the time of OTS culture before starting the actual experiment is shorter (1 week) [25,26]; so the mechanical damage caused by slicing disappears, and the cells can reach a more advanced developmental stage. In addition, this time period will allow the slices to acclimatize to the culturing conditions and mature.…”
Section: Organotypic Slicesmentioning
confidence: 99%
“…Early postnatal periods (P0-P9) are ideally suited for culturing [26,39,42]. Since most diseases of the spinal cord concern the adults, some organotypic spinal cord slice culture models from grown rats were established [25,26].…”
Section: Age Of Donor Animalmentioning
confidence: 99%
See 1 more Smart Citation
“…; Sypecka et al. ). The organotypic slice culture (OSC) model appears to reproduce much of the post‐traumatic events following injury, including acute and secondary injury mechanisms.…”
Section: Introductionmentioning
confidence: 97%
“…Cell death is one of the consequences of traumatic SCI, affecting both neurons and supporting glial cells (Beattie et al 2002). Numerous studies have reported spinal cord tissue samples isolated from embryonic or newborn rats (Krassioukov et al 2002;Cho et al 2009;Kim et al 2010;Ravikumar et al 2012;Gerardo-Nava et al 2013Pinkernelle et al 2013;Hashemian et al 2014;Weightman et al 2014;Pohland et al 2015;Sypecka et al 2015). The organotypic slice culture (OSC) model appears to reproduce much of the post-traumatic events following injury, including acute and secondary injury mechanisms.…”
Section: Introductionmentioning
confidence: 99%